External validation of a prognostic score predicting overall survival for patients with brain metastases based on extracranial factors. (May 2019) - Lewitzki, Victor; Klement, Rainer J.; Hess, Sebastian; Kosmala, Rebekka; Nieder, Carsten; Flentje, Michael
Highlights: We provide an external validation of the extracranial prognostic score developed by Nieder et al. This extracranial score could effectively define the patients with very short survival. A new combination of extracranial score with DS-GPA-score achieved an even better discrimination Abstract : Purpose: The aim of our study was an external validation of the extracranial prognostic score predicting survival of patients with brain metastases receiving cranial irradiation on data from a single institution. Materials and methods: A retrospective analysis of 524 patients with brain metastases treated with cranial radiotherapy in a single tertiary center was performed. Three predictive scores were calculated and assessed for their ability to discriminate prognostic groups: (i) The Recursive Partitioning Analysis (RPA) score (available for 524 patients); (ii) the Diagnosis-Specific Graded Prognostic Assessment (DS-GPA) score (464 patients); (iii) the extracranial score (EC-S) developed by Nieder et al. which is based on serum albumin, lactate dehydrogenase (LDH) and the number of extracranial organs involved (157 patients). Discrimination of each score was assessed by Gönen & Heller's concordance probability estimate (CPE). The calibration was checked by comparing median survival estimates of each risk group with the corresponding values of the datasets from which the scores were derived. Finally, a multivariable Cox regression model was built by using the least absolute shrinkage and selection operator on a large number of variables including all three scores. Results: With a CPE = 0.626 ± 0.022, the EC-S had the best discriminatory power. The EC-S also appeared to be better calibrated and had the best ability to separate patients with a very poor prognosis: patients with combination of low albumin, elevated LDH and more than 1 extracranial organ with metastatic involvement had a median survival time of only 0.6 months (CI95% 0.1–1.1) and a hazard ratio for death of 6.36 (2.67–15.14) compared to patients with no extracranial metastases and normal levels of albumin and LDH. In the multivariable Cox model serum albumin, LDH, treatment modality, DS-GPA and EC-S were retained as prognostic factors. An ad hoc combination of both DS-GPA and EC-S into a new score was possible for 134 patients and indicated a slightly better discrimination (CPE = 0.636 ± 0.023) than either DS-GPA or EC-S alone. Conclusions: This study provides an independent validation of the prognostic EC-S which was the best prognostic model for defining the patients who obviously did not benefit from radiation therapy of brain metastases in terms of overall survival. The combination of the EC-S with the established DS-GPA score resulted in a slight increase in discriminatory ability. The new EC-GPA score needs further validation in larger patient cohorts.